From Microbial Homeostasis to Systemic Pathogenesis: A Narrative Review on Gut Flora’s Role in Neuropsychiatric, Metabolic, and Cancer Disorders - Yan X; Shi L; Zhu X; Zhao Y; Luo J; Li Q; Xu Z; Zhao J (Journal of Inflammation Research)
Xili Yan,1,2,* Liangbin Shi,1,2,* Xiuling Zhu,2 Yingdi Zhao,2 Jie Luo,3 Qiang Li,4 Zhiliang Xu,2,5 Jian Zhao2 1School of Graduate Medicine, Wannan Medical College, Wuhu, Anhui, 241002, People’s Republic of China; 2Department of Human Anatomy, School of Basic Medical Science, Wannan Medical College, Wuhu, Anhui, 241002, People’s Republic of China; 3School of Clinical Medicine, Wannan Medical College, Wuhu, Anhui, 241002, People’s Republic of China; 4Human Anatomy Experimental Training Center, School of Basic Medical Science, Wannan Medical College, Wuhu, Anhui, 241002, People’s Republic of China; 5Anhui Province Key Laboratory of Basic Research and Translation of Aging-Related Diseases, Wannan Medical College, Wuhu, Anhui, 241002, People’s Republic of China*These authors contributed equally to this workCorrespondence: Jian Zhao; Zhiliang Xu, Email zhaojian@wnmc.edu.cn; xuzhiliang2010@foxmail.comAbstract: As a pivotal ecological regulator in humans, the gut microbiota profoundly participates in the pathological processes of neurodegenerative diseases, psychiatric disorders, metabolic syndromes, and cancers through metabolite exchange, epigenetic regulation, and gut-brain axis signaling. This review focuses on analyzing relationships between gut microbial communities and four major disease spectra: neurodegenerative diseases (Alzheimer’s disease, Parkinson’s disease, Huntington’s disease)—revealing microbiota-derived lipopolysaccharide activation of microglia and gut-brain transmission pathways of α-synuclein; mental health disorders (depression, schizophrenia, bipolar disorder)—elucidating dysregulated tryptophan metabolism and gut-derived neurotransmitter imbalances; metabolic diseases (obesity, diabetes, gout)—analyzing molecular mechanisms by which short-chain fatty acids regulate insulin sensitivity and uric acid metabolism; malignant tumors (lung cancer, breast cancer, prostate cancer)—exploring microbial remodeling of immune checkpoint inhibitor responses and regulatory effects on estrogen metabolism. We integrate existing evidence to systematically expound the roles of gut microbiota alterations in the pathogenesis of neurodegenerative diseases, psychiatric disorders, metabolic dysregulation, and malignant tumors, with in-depth analysis of mechanisms through which dysbiosis promotes disease progression, aiming to provide a theoretical foundation and scientific recommendations for developing microbiota-targeted precision intervention strategies (including, but not limited to synthetic microbial community transplantation and metabolite-directed regulation).Keywords: microbiota, immune regulation, neuromodulation, metabolic balance, imbalance of intestinal flora homeostasis